2011
DOI: 10.14742/ajet.970
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating computer-based simulations, multimedia and animations that help integrate blended learning with lectures in first year statistics

Abstract: The discipline of statistics seems well suited to the integration of technology in a lecture as a means to enhance student learning and engagement. Technology can be used to simulate statistical concepts, create interactive learning exercises, and illustrate real world applications of statistics. The present study aimed to better understand the use of such applications during lectures from the student's perspective. The technology used included multimedia, computer-based simulations, animations, and statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 36 publications
4
37
0
3
Order By: Relevance
“…The overall results appear to support the data that computer simulations are most effective when used as a supplement to face-to-face lectures and in hybrid environments (Koh et al, 2010;Mkpanang, 2010;Mosalanejad et al, 2012;Neumann et al, 2011).…”
Section: Discussionsupporting
confidence: 72%
“…The overall results appear to support the data that computer simulations are most effective when used as a supplement to face-to-face lectures and in hybrid environments (Koh et al, 2010;Mkpanang, 2010;Mosalanejad et al, 2012;Neumann et al, 2011).…”
Section: Discussionsupporting
confidence: 72%
“…The integration of technology also provides a means to enhance student learning and engagement in lectures. Therefore, recent studies have aimed to better understand the applications adapted during lectures from the perspective of students, including multimedia, computer-based simulations, animations and statistical software (Neumann et al, 2011). Research by Geer and Sweeney (2012) showed that the use of a variety of media applications to explain concepts increased the understanding and supported greater collaboration between students.…”
Section: Introductionmentioning
confidence: 99%
“…In specific areas of the curriculum, software may provide opportunities for computer based simulation of techniques, tools for handling large sets of authentic data, as in the teaching of statistics e.g. Neumann, Neumann, & Hood, 2011, and for widening the range of 'accessible geometrical constructions', as in Straesser's (2002) discussion of Cabri. Of course there is not universal agreement as to the value of technology.…”
Section: Background To the Studymentioning
confidence: 99%